2010
DOI: 10.1007/s10826-010-9384-5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Perceptions of Family Connectedness, Intrinsic Religiosity, and Depressed Mood

Abstract: Using a sample of 248 ninth and tenth grade students at public high schools, we examined adolescents' perceptions of family connectedness, intrinsic religiosity, and adolescents' gender in relation to depressed mood and whether intrinsic religiosity and gender moderated the association of aspects of family connectedness to adolescent depressed mood. Using hierarchical multiple regression analyses we tested models separately for three forms of family connectedness (overall family cohesion, mothers' support, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
2
28
0
2
Order By: Relevance
“…Consistent with previous studies [21] [23] [24], the present study found weak to moderate, but significant bivariate correlations between depression and social support, religiosity, and spirituality; an indication that social support, frequent participation in religious activities, and spiritual interconnectedness are good for mental and emotional well-being of adolescents. Yet, in some other studies, some aspects of religiosity such as private religious practices were not associated with depression in adolescents [26] [31] [33].…”
Section: Major Findings Of the Studymentioning
confidence: 96%
See 2 more Smart Citations
“…Consistent with previous studies [21] [23] [24], the present study found weak to moderate, but significant bivariate correlations between depression and social support, religiosity, and spirituality; an indication that social support, frequent participation in religious activities, and spiritual interconnectedness are good for mental and emotional well-being of adolescents. Yet, in some other studies, some aspects of religiosity such as private religious practices were not associated with depression in adolescents [26] [31] [33].…”
Section: Major Findings Of the Studymentioning
confidence: 96%
“…The relationship between adolescent depression and social support has been extensively investigated in empirical studies. Higher levels of friend support, family support, and overall emotional support have been consistently associated with lower odds of adolescent depression [21] [26] [27] [28]. Social relationships may promote well-being by enhancing an individual's feelings of predictability and stability, maintaining positive emotional states, promoting an individual's sense of purpose, belonging, and security and enhancing self-esteem through social recognition of self-worth [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pero, si bien inicialmente esta distinción acerca de las orientaciones religiosas se fundamentó en distinguir aquellos tipos de religiosidad que podían presentar una mayor tendencia al prejuicio de aquellos que no, posteriormente se produjo una expansión en cuanto a los beneficios de comprender con mayor profundidad el fenómeno de la religiosidad en relación a otras áreas de la psicología, como la salud mental (Maltby, 2002). Por ejemplo, existen trabajos que señalan cómo las orientaciones religiosas permiten favorecer la calidad de vida de pacientes terminales (Piedmont & Friedman, 2012), afrontar el estrés (Laufer & Solomon, 2011;McMahon & Biggs, 2012), la depresión (Davison, McCabe, Knight & Mellor, 2012;Houltberg, Henry, Merten & Robinson, 2011) o la ansiedad (Maltby et al, 2010).…”
Section: Conclusiónunclassified
“…Maternal and paternal emotional support are significantly associated with adolescent depressive symptoms (Houltberg, Henry, Merten, & Robinson, 2011) and lower levels of positive parental behaviors have prospectively predicted adolescent depressive symptoms at a 2.5 year follow-up (Schwartz et al, 2012). Low levels of parental support have been found to correlate amongst adolescents and young adults experiencing high levels of depressive symptoms (i.e., Holahan et al, 1995;Pettit et al, 2011;Stice et al, 2004).…”
Section: Explanations Concerning Etiological Relationships Though Almentioning
confidence: 99%